CHANGES IN CELL-MEDIATED AND HUMORAL IMMUNITY INDICES AND LEVELS OF PRO- AND ANTI-INFLAMMATORY CYTOKINES IN CERVICAL MUCUS IN PREGNANT WOMEN OF HIGH RISK FOR PREECLAMPSIA - Likhachov, V.K.; Vashchenko, V.L.; Taranovska O.О.; Dobrovolska, L.M.; Makarov, O.G. (World of Medicine and Biology, 2021)
62 pregnant women were examined, of which 30 were healthy pregnant ones (control group) and 32 women at high risk of preeclampsia (main group – MG) at 18–20 + 6 weeks and 28–32 weeks of pregnancy. The content of pro- and anti-inflammatory cytokines (TNFα, INFγ, IL10) in cervical mucus and indices of cellular-humoral immunity in the blood, including the concentration of circulating immune complexes (CIC) in the serum were studied. The analysis of the subpopulation composition of T - cells revealed a decrease in the concentration of T-helpers (CD4+) with a significant increase in the concentration of T-suppressors/killers (CD8+) with a corresponding decrease in the immunoregulatory index. A significant decrease in the number of B cells (CD22+) was registered. An increase in CIC in the main group of subjects was demonstrated, and an increase in CIC levels above 100 IU/ml was closely associated with the development of preeclampsia. IgM in women with preeclampsia was significantly elevated, which may indicate the presence of trophoblastic stimulation of the immune system in these women. IgG levels were significantly reduced. In women with preeclampsia, a significant predominance of pro-inflammatory cytokines has been found in anti-inflammatory cytokine deficiency.